A case of neural integrity monitor endotracheal tube malfunction: What to blame? Cancelled surgery due to NIM tracheal tube malfunction e a case report - Abdulrahman Dardeer (15900223) (2023)
Intraoperative neuromonitoring of the recurrent laryngeal nerve (RLN) is becoming the standard of care in surgeries of the brainstem, skull base, thyroid, and parathyroid with the potential risk for RLN damage. The Neural Integrity Monitor (NIM) endotracheal tube is a specialized tube that utilizes electromyography (EMG) for identifying the RLN intraoperatively. Vocal cords movement (if the touched structure is a nerve) is captured and shown on a monitor visually with a distinctive sound to alert the team. We describe a case of recurrent thyroid papillary carcinoma who needed surgical intervention for the third time, in which a NIM tube was used. After careful troubleshooting and failure to solve the issue, the artefacts were attributed to the patient's dental retainers (braces). The surgery was aborted. Subsequently, several tests were done on dental models with and without braces using the very NIM tube used on the patient. Our tests showed no difference in artefacts, suggesting a faulty NIM tube. However, no research, evidence, or manufacturer recommendations exist related to the use of the NIM ETT with dental retainers. There is no evidence suggesting signal interference due to metal braces. The surgery was carried out uneventfully on a subsequent day with a new NIM tube. Other Information Published in: Trends in Anaesthesia and Critical Care License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.tacc.2023.101259